2022
DOI: 10.1155/2022/4812993
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Age-Related Multiple Neuronal Impairments and Inflammation in High-Fat Diet-Fed Rats: The Prospective Multitargets of Geraniol

Abstract: Neuroinflammation is documented to alter brain function as a consequence of metabolic changes linked with a high-fat diet (HFD). The primary target of this study is to see how geraniol is effective in manipulating age- and diet-associated multiple toxicity and neuroinflammation in HFD-fed rats. Sixty-four adult male Wistar rats were partitioned into two groups: Group 1 (untreated normal young and aged rats) and Group 2 (HFD-fed young and aged rats) that received HFD for 16 weeks before being orally treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Exercise affects muscle function by modifying exercise-responsive gene expression (i.e., PGC-1α, TFAM, and MEF2A), even after exercise, triggering structural and metabolic adaptations in skeletal muscles 68 . Also, it mediated muscle health and longevity through sirtuin-1-regulated pathways and the regulation of PGC-1α, the master controller of mitochondrial biogenesis 30 . Mitochondrial morphological changes decrease inflammatory and oxidative states in old age due to increasing nuclear respiratory factor (NRF-1) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise affects muscle function by modifying exercise-responsive gene expression (i.e., PGC-1α, TFAM, and MEF2A), even after exercise, triggering structural and metabolic adaptations in skeletal muscles 68 . Also, it mediated muscle health and longevity through sirtuin-1-regulated pathways and the regulation of PGC-1α, the master controller of mitochondrial biogenesis 30 . Mitochondrial morphological changes decrease inflammatory and oxidative states in old age due to increasing nuclear respiratory factor (NRF-1) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our molecular docking results showed that linalool and geraniol exhibited low affinity to FADS2, CD36, and ACCA1 (Table 2). However, previous studies have demonstrated that linalool and geraniol can inhibit liver injury through antioxidant signaling pathways (El Azab & Abdulmalek, 2022;Hsouna et al, 2022;Miao et al, 2022). Furthermore, both compounds have broad-spectrum antibacterial effects (Gu et al, 2022;Li, He, et al, 2022;Li, Ren, et al, 2022) and the potential to modulate the gut microbiota (Ricci et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in vivo, geraniol improved neuroinflammation and oxidative stress, as well as cognitive skills, in mice fed with a high-fat diet prior to drug treatment [113].…”
Section: Thymus Vulgaris Eomentioning
confidence: 95%